Predation of domestic dogs (Canis lupus familiaris) on Schlegel’s banded langur (Presbytis neglectus) and crested hawk-eagle (Nisaetus cirrhatus) on dusky leaf monkey (Trachypithecus obscurus) in Malaysia. - Najmuddin, Mohd Faudzir; Hidayah, Haris; Noratiqah, Norazlimi; Badrul Munir, Md Zain; Mohd Ridwan, Abd Rahman; Rohani, Shahrool Annuar; Asiyahtul Husna, Hassan; Abdul Latiff, Muhammad Abu Bakar (UMT Publisher, 2019)
Predations on primates are rarely documented despite being an important survival challenges for such animal. In Johor, Malaysia, Schlegel’s banded langur (Presbytis neglectus) and dusky leaf monkey (Trachypithecus obscurus) are not exempted from the present threats. Here we describe the predation of Schlegel’s banded langur (P. neglectus) by domestic dogs (Canis lupus familiaris) and unsuccessful predation of dusky leaf monkey (T. obscurus) by crested hawk-eagle (Nisaetus cirrhatus). Our observation reported two chasing attempts followed by two successful predations of banded langur by domestic dogs and an unsuccessful predation on dusky leaf monkey (T. obscurus) juvenile by crested hawk-eagle (N. cirrhatus). This is the first ever report on predation of banded langur (P. neglectus) by terrestrial animal and act as a significance standpoint in ecology and conservation of langurs